Effects of cold storage on detection of avian infectious bronchitis virus in chicken carcasses and local antibodies in tracheal washes - Ganapathy, Kannan (J Virol Methods, 2005)
In order to test the survivability of infectious bronchitis virus (IBV) in dead chicken carcasses during 24 h of cold storage, 7 week-old specific-pathogen-free chickens were infected with virulent IBV Massachusetts strain M41, and were killed humanely 10 days later. Carcasses were stored in a cold room at 4 °C. After 1, 3, 6, 9, 12 or 24 h of storage, necropsies were carried out. Trachea, lung, kidney and rectum were collected for virus isolation by tracheal organ culture (TOC) or embryonated chicken eggs (ECE), and detection by nested reverse-transcriptase polymerase chain reaction (RT-PCR). IBV was detected by RT-PCR at all sampling times, except for 1 and 6 h of storage in kidney and 9 h of storage in kidney and rectum. For ECE, isolation was obtained at all sampling points, except at 1 and 24 h of storage in lungs. Isolation by tracheal organ cultures was less successful, except from rectum. In addition to sampling for virus, tracheal washes were collected from each carcass to measure the ability to detect local antibodies after storage. Levels of IgA in tracheal washes remained high for up to 9 h of storage, suggesting that accurate sampling for research purposes when required must be carried out within this time.